Phylogenetic analysis of the viral proteins VP4/VP7 of circulating human rotavirus strains in China from 2016 to 2019 and comparison of their antigenic epitopes with those of vaccine strains - Mao, Tongyao; Wang, Mengxuan; Wang, Jindong; Ma, Yalin; Liu, Xiafei; Wang, Mingwen; Sun, Xiaoman; Li, Lili; Li, Huiying; Zhang, Qing; Li, Dandi; Duan, Zhaojun (Frontiers in Cellular and Infection Microbiology, 2022)
Group A rotaviruses (RVAs) are the most commonly recognized etiological agents of severe acute diarrhea among children under 5 years old worldwide. At present, two live-attenuated rotavirus group A (RVA) vaccines, LLR (G10P[15]) and RotaTeq(G1-G4,G6 P[8],P[5]), have been successfully introduced in mainland of China. Although RVA vaccine can provide homotypic and partially heterotypic protection for different strains, it is also necessary to explore the genetic and antigenic variation between circulating RVAs and the vaccine strains. In this study, we sequenced the VP7 and VP4 outer capsid proteins of 50 RVAs strains circulating in China during 2016 to 2019. The VP7 and VP4 sequence of almost all strains show high homology with that of previously reported human strains and vaccine strains in same genotype. However, in the presumed antigenic epitopes of the VP7 and VP4, multiple amino acids variations were found, regardless of G and P genotypes of these strains. Moreover, all circulating G3 RVA strains in China were found to possibly possess an extra N-linked glycosylation site (NSS) compared to the G3 strain of RotaTeq. Potential NSS of site 69-71 were found in all G9 strain of China but not in Rotavac and Rotasill vaccine with G9. These variations in antigenic sites might result in selection for strains that escape the RVA neutralizing-antibody pressure imposed by vaccines. Furthermore, The G4 and P[6] genotypes in this study showed high homology with porcine strains, which indicates the transmission of G4 and P[6] genotypes from porcine to human in China. More genetic surveillance with antigenic evaluation in prevalent RVA is necessary for development and implementation of rotavirus vaccine in China